Gambaran skor MMSE dan MoCA-INA pada pasien cedera kepala ringan dan sedang yang dirawat di RSUP Prof. Dr. R. D. Kandou Manado - Athika, Nurindah; PS, Junita Maja; Mawuntu, Arthur H.P. (Universitas Sam Ratulangi, 2016)
Abstract: Traumatic Brain Injury (TBI) is the most common case in hospital. TBI can caused cognitive impairment. This study aimed to obtain the description of cognitive function in patients with mild and moderate TBI that were admitted to Prof. Dr. R. D. Kandou Hospital Manado. This was a prospective descriptive study by conducting direct examination to the patients diagnosed with mild or moderate TBI by using MMSE and Ina MoCA instruments. Thee results showed that there of 50 subjects there were 74% with mild TBI and 26% with moderate TBI. MMSE showed 96% normal while Ina MoCA showed 76% normal. Cognitive function impairment was more visible on Ina MoCA examination. Conclusion: Ina MoCA was better than MMSE examination in description of cognitive function impairment.Keywords: head injury, cognitive functionÂ Abstrak: Cedera kepala merupakan suatu kegawatan yang paling sering dijumpai di Rumah Sakit. Cedera kepala dapat menyebabkan gangguan fungsi kognitif. Penelitian ini bertujuan untuk mengetahui gambaran skor MMSE dan MoCA-Ina pada pasien cedera kepala ringan dan sedang yang dirawat di RSUP Prof. Dr. R. D. Kandou Manado. Jenis penelitian ini ialah deskriptif prospektif dengan melakukan pemeriksaan langsung pada pasien yang didiagnosis cedera kepala ringan atau sedang menggunakan instrumen MMSE dan MoCA-Ina. Hasil penelitian mendapatkan subjek sebanyak 50 orang dengan persentase cedera kepala ringan sebanyak 74% dan cedera kepala sedang 26%. Pada MMSE didapatkan 96% normal sedangkan pada MoCA-Ina didapatkan 76% normal. Penurunan fungsi kognitif lebih terlihat pada pemeriksaan MoCA-Ina. Simpulan: MoCA-Ina lebih dapat menggambarkan gangguan fungsi kognitif daripada pemeriksaan MMSE. Kata kunci: cedera kepala, fungsi kognitif